Protecting society: Biological security and dual‐use dilemma in the life sciences—status quo and options for the future. (11th December 2012) - Uhlenhaut, Christine; Burger, Reinhard; Schaade, Lars
Abstract : Concerns over biosecurity remain unresolved, as the debate around the recent publications on human transmissible H5N1 flu demonstrated. A range of measures and the involvement of all stakeholders are needed to better protect society from malicious abuse of biological research.